2010
DOI: 10.1021/pr9011602
|View full text |Cite
|
Sign up to set email alerts
|

Multimethodological Approach to Identification of Glycoproteins from the Proteome of Francisella tularensis, an Intracellular Microorganism

Abstract: It appears that most glycoproteins found in pathogenic bacteria are associated with virulence. Despite the recent identification of novel virulence factors, the mechanisms of virulence in Francisella tularensis are poorly understood. In spite of its importance, questions about glycosylation of proteins in this bacterium and its potential connection with bacterial virulence have not been answered yet. In the present study, several putative Francisella tularensis glycoproteins were characterized through the comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 45 publications
1
57
1
Order By: Relevance
“…In many cases, extensive structural characterizations of bacterial glycoproteins have been completed, but research on the biological significance and utility of these novel glycoconjugates is in its infancy. Recent reports have suggested that strains of Francisella elaborate glycoproteins (3,41). Here we show that the putative disulfide isomerase protein and essential virulence factor, DsbA, is modified in O-linkage with a hexasaccharide moiety.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In many cases, extensive structural characterizations of bacterial glycoproteins have been completed, but research on the biological significance and utility of these novel glycoconjugates is in its infancy. Recent reports have suggested that strains of Francisella elaborate glycoproteins (3,41). Here we show that the putative disulfide isomerase protein and essential virulence factor, DsbA, is modified in O-linkage with a hexasaccharide moiety.…”
Section: Discussionmentioning
confidence: 54%
“…The same is true for several peptide fragment ions at either end of the sequence that are subject to both ␤-elimination and deamidation. Additionally, a gas phase neutral loss of NH 3 To confirm that FTT0798 and FTT0791 were not involved in the biosynthesis of the O antigen, lipopolysaccharide (LPS) profiles of the ⌬FTT0791::Cm and ⌬FTT0798 mutants were analyzed by Western blotting using a monoclonal antibody to F. tularensis subsp. tularensis LPS (Fig.…”
Section: F Tularensis Subsp Tularensis Strain Schus4mentioning
confidence: 99%
“…Apart from the pilin, other proteins linked to virulence were also found to be glycosylated. Balonova (510). Of note, many of these proteins were also identified by Janovska et al (511) as immunoreactive antigens in the live vaccine strain (LVS) of F. tularensis subsp.…”
Section: Protein Glycosylationmentioning
confidence: 79%
“…However, their functional importance can be even more vi-brant than currently appreciated. For instance, several groups reported the (potential) glycosylation of proteins involved in the multienzyme complexes of the cell wall biosynthesis and division machinery (270,510,569). It is tempting to speculate that the as-yet-unexplored glycosylation of major enzymes in these complexes could play a role in the regulation of their interaction and activity, but this remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of FTS_1067 protein in the cell lysate of complemented strain was confirmed by immunodetection using either Anti-FLAG M2 monoclonal antibody or polyclonal antibody raised against FTS_1067 protein (Figure 1). The theoretical molecular weight of FTS_1067 is 39 kDa, but it is known that the protein is post-translationally modified by glycosylation [20,21], which increases its molecular weight. We detected the protein band migrating around 50 kDa by both antibodies, proving that the protein FTS_1067 is produced in the complemented strain.…”
Section: Resultsmentioning
confidence: 99%